شهر الدعاوى القضائية- بين التأشير الهامشي والاشهار - حويذق, عثمان (University of Eloued جامعة الوادي, 2020)
لقد اشترط المشرع الجزائري ضرورة إشهار الدعوى القضائية إذا كان محل المنازعة حق عيني عقاري مشهر، وهذا حماية للغير حسن النية من جهة ولكي يؤدي الشهر وظيفته المرجوّة منه من خلال إعلام الكافة بكل ما يتعلق بهذا العقار. تم إعتماد التأشير الهامشي كآلية لإشهار الدعوى القضائية ، لكن تم مؤخرا وبعد صدور قانون المالية لسنة 2019 التأكيد على ضرورة القيام بإشهار العرائض القضائية المحددة بنصوص قانونية على سبيل الحصر ، وهذا الإشهار لا يقيد التصرف في العقار المثقل بعرائض قضائية، لكن يجب التبليغ الرسمي للمتصرف إليه قبل إبرام العقد، حماية لحقوق جميع الأطراف على حد سواء.It is required by the Algerian legislator that the lawsuit should be registered if the subject in dispute is a registered real estate related right and this is to protect the bona fide third parties on one hand, and for the registration to perform its desired function by informing everyone about everything related to the property in dispute on the other hand. Marginal notation was adopted as a mechanism for registering lawsuits until recently, after the issuance of the Finance Law in which required the registration of the judicial petitions exclusively specified by legal texts. This registration does not restrict the transfer of the real estate burdened with judicial petitions but stipulates the official notication the transferee before concluding the contract to protect the rights of all parties involved.
Publicity; Lawsuit; Marginal Notation; Lawsuit Registration; Notifying the Transferee
مقال
Keywords: الشهر ; القضائية ; التاشير الهامشي ; إشهار ; تبليغ المتصرف اليه; Publicity; Lawsuit; Marginal Notation; Lawsuit Registration; Notifying the Transferee